2010
DOI: 10.1021/ja100464a
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Order, Nanocrystal Size, and Capping Ligands in the Collective Mechanical Response of Three-Dimensional Nanocrystal Solids

Abstract: Chemically synthesized PbS, CdSe, and CoPt(3) nanocrystals (NCs) were self-assembled into highly periodic supercrystals. Using the combination of small-angle X-ray scattering, X-ray photoelectron spectroscopy, infrared spectroscopy, thermogravimetric analysis, and nanoindentation, we correlated the mechanical properties of the supercrystals with the NC size, capping ligands, and degree of ordering. We found that such structures have elastic moduli and hardnesses in the range of approximately 0.2-6 GPa and 10-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
190
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(220 citation statements)
references
References 60 publications
25
190
4
Order By: Relevance
“…In such conditions, the van der Waals interactions between the cores increase on increasing the NCs and consequently the Young modulus also increases. This interpretation agrees with that of Podsiadlo et al [23]. From simulations and experiments, the coverage of alkanethiol on Au NCs decreases on the increase of the NCs size [40][41][42].…”
Section: Size Effect Of the Building Blocks (Ncs) Used To Producesupporting
confidence: 92%
See 2 more Smart Citations
“…In such conditions, the van der Waals interactions between the cores increase on increasing the NCs and consequently the Young modulus also increases. This interpretation agrees with that of Podsiadlo et al [23]. From simulations and experiments, the coverage of alkanethiol on Au NCs decreases on the increase of the NCs size [40][41][42].…”
Section: Size Effect Of the Building Blocks (Ncs) Used To Producesupporting
confidence: 92%
“…Note that these data are highly reproducible. Furthermore Podsiadlo et al [23] found an increase in Young's modulus with increasing PbS NCs size coated with oleic acid. These marked changes could be attributed to the ligand-ligand and ligand-atoms interactions.…”
Section: Size Effect Of the Building Blocks (Ncs) Used To Producementioning
confidence: 95%
See 1 more Smart Citation
“…4). The elastic moduli measured here are comparable to the values for nanocrystal arrays containing short, alkyl ligands measured through AFM membrane deflection (7)(8)(9) and nanoindentation (19)(20)(21), and are higher than the modulus of polystyrene-grafted silica nanoparticle films with similar polymer molecular weight and concentrated polymer brushes (24). The Halpin-Tsai model was used to separate the contribution of the polymeric and inorganic components to the superlattice elastic modulus in superlattices prepared at RT-covered (38,47).…”
Section: Resultssupporting
confidence: 64%
“…This class of superlattices provides an ideal framework for developing a mechanistic understanding of the novel mechanical properties of nanocrystal superlattices because superlattice structure, dimensions, and ligand length can be varied across a wide range of conditions and the effect of each of these parameters can be independently evaluated. In comparison, previous work showed that the elastic modulus, ductility, and hardness of nanocrystal arrays are influenced by ligand and nanocrystal type, and nanocrystal packing, but the alkyl ligands in these studies differed in length only by a few carboncarbon bonds, and structural variations were not quantified (7,9,(19)(20)(21). Polymer-grafted nanocrystal superlattices also differ from composites made from nanoparticles grafted to polymers with lengths of tens to thousands of monomers, because these composites usually contain aggregates or randomly dispersed nanoparticles instead of precisely ordered, periodic microstructures (22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 67%